Verbal Communication with Second Language Toward Children Fear in Dental Care - Listyo Rinawati; Ani Subekti (Jurnal Kesehatan Gigi, 2022)
Good verbal communicating with children can use phrases or words - a substitute word that connotes not painful and terrible (second language), so that the child can receive dental treatment. This study to know the effect of using a second language toward children fear in dental care. Samples are 4-6 years old pediatric patients who came in dental clinic Listyo Rinawati on Johor Malaysia. Measurement of children fear on dental care is scaled Venham's Clinical Ratings. The results showed in the intervention group second language is 100% of children experience fear level changes according to the scale Venham's Clinical Ratings. There are 45% who were initially reluctant to change it to relax. In children without giving a second language showed 35% had only reluctantly and turned decreased by 25%. The results of the independent T-test are sig. 0.00 0.05 which means that there are differences in fear in the two groups of different treatments. Verbal communication with a second language may help overcome the fear of the child before and during dental treatment, dental treatment of children that will be successful and the child will not be afraid to make a visit next dental care.